DIABETES MELLITUS AND MENOPAUSE - Khaydarova Zarrina Erkinovna; Khusainova Munira Alisherovna; Khaydarov Sanjar Nizamitdinovich (Journals Park Publishing, 2024)
A study was performed to determine the effect of drospirenone, which is part of the low-dose drug Angelik, on carbohydrate metabolism and hemostasis in postmenopausal patients with type 2 diabetes mellitus. 50 patients with menopausal syndrome who are in natural menopause, duration of more than 2 years old, suffering from type 2 diabetes mellitus. 30 women who do not have contraindications are prescribed the low-dose drug Angelik. Indicators of carbohydrate metabolism were assessed by fasting glucose, C-peptide, insulin, insulin resistance was calculated by the Nomo index, hemostasis indicators by platelet level, coagulogram, D-dimer initially, after 3 and 6 months of treatment. During treatment with Angelik, there was a significant decrease in glucose and insulin resistance by the 6th month of administration, and no effect on the state of the hemostasis system. The obtained data allow us to recommend Angelik drug for hormone replacement therapy in postmenopausal patients suffering from type 2 diabetes mellitus as effective, safe and possessing a number of additional positive properties.
Keywords: menopausal syndrome, type 2 diabetes mellitus, hormone replacement therapy, carbohydrate metabolism, hemostasis.